Spatial statistics & geostatistics : theory and applications for geographic information science & technology - Chun, Yongwan; Griffith, Daniel A. (Los Angeles : SAGE, 2013)
Its focus is on spatial statistics as a distinct form of statistical analysis and it includes computer components for ArcGIS, R, SAS, and WinBUGS. The teaching and learning objective of the text is to illustrate the use of basic spatial statistics, geostatistics and the spatial filtering techniques used in all the relevant programs and software.
Introduction -- Spatial autocorrelation -- Spatial sampling -- Spatial composition and configuration -- Spatially adjusted regression and related spatial econometrics -- Local statistics: hot and cold spots -- Analyzing spatial variance and covariance with geostatistics and related techniques -- Methods for spatial interpolation in two dimensions -- More advanced topics in spatial statistics.
"GIST"
Includes bibliographical references (p. [169]-173) and index.
Keywords: Geospatial data; SPATIAL ANALYSIS; STATISTICS